A Randomized Clinical Trial on the Efficacy of Siravedhana and Kumkumadi Ghrita Nasya along with Chandrakanta Rasa Orally in Ardhavabhedaka w. s. r. to Migraine - Nayak, Ajay Kumar; Fiaz , Shamsa (International Research Journal of Ayurveda & Yoga, 2020)
Background: Migraine is a form of primary headache, manifested by the recurrent attacks of pulsating headache, mostly associated with nausea, vomiting, photophobia and phonophobia with or without an aura. It is the second most common cause of headache disorder affecting about 12%. In this females are most prone 15% and males are affecting about 6%. On the basis of the symptoms of Ardhavabhedaka, it can be correlated with Migraine. Aim and objectives: To conduct a randomized clinical trial on Kumkumadi Ghrita Nasya and Siravedhana along with Chandrakanta Rasa in the management of Ardhavbhedaka w.s.r. to Migraine. Material and method: Patients attending the O.P.D. and I.P.D. of N.I.A. having the signs and symptoms of Ardhavbhedaka (Migraine) were screened and the diagnosis was achieved on the basis of careful history taking and clinical examination. 30 clinically diagnosed patients of Ardhavbhedaka were registered for trial and they were divided randomly in two groups. Result: Clinical data shows that in Group A effect of therapy on Ardhavbhedhaka is 74.91% and in Group B it is 63.93%; both the results are statistically highly significant at the level of p < 0.001. Conclusion: It can be concluded that clinically Siravedha, Kumkumadi Ghrita Nasya and Chandrakanta Rasa combine work better to manage the Ardhavabhedaka (Migraine).